## Solving the Equation (x+1)(x+1) - (x-1)(x-1) = 4

This equation involves simplifying and solving for the unknown variable 'x'. Let's break down the steps:

### 1. Expanding the Equation

First, we need to expand the expressions on both sides of the equation:

**(x+1)(x+1)**can be expanded using the FOIL method (First, Outer, Inner, Last):- x * x + x * 1 + 1 * x + 1 * 1 =
**x² + 2x + 1**

- x * x + x * 1 + 1 * x + 1 * 1 =
**(x-1)(x-1)**can also be expanded using the FOIL method:- x * x + x * -1 + -1 * x + -1 * -1 =
**x² - 2x + 1**

- x * x + x * -1 + -1 * x + -1 * -1 =

Now our equation looks like this: **x² + 2x + 1 - (x² - 2x + 1) = 4**

### 2. Simplifying the Equation

Next, we can simplify the equation by removing the parentheses and combining like terms:

- x² + 2x + 1 - x² + 2x - 1 = 4
**4x = 4**

### 3. Solving for 'x'

Finally, we can solve for 'x' by dividing both sides of the equation by 4:

**x = 1**

### Solution

Therefore, the solution to the equation (x+1)(x+1) - (x-1)(x-1) = 4 is **x = 1**.